DAKWAH SOSIAL EKONOMI DALAM PANDANGAN DAWAM RAHARDJO - Ma'mun Efendi Nur (Jurnal Ilmu Dakwah, 2017)
Islam is a humanism, a religion that is very concerned with human being as a center destination. This characteristic of Islam brings the consequence that this perfect religion is very big role for human, not only regulate and contain messages that must be implemented in vertical line to God, even role to regulate social life - relative horizontal - as well as other fields such as social, economy, politics , health, culture and so on. Dawam Rahardjo, one of the leading figures of Islamic and Modern Economics, has a view and activity in the field of social economic transformation of dakwah focused on four points (Islamic Economy, Main Society, Zakat and Islamic Self-Help and Work Ethic in Islam), each peeled deeply and applicative, which is his view and experience. Nevertheless each view is inseparable from the advantages and disadvantages